Cities in federal constitutional theory - Arban, Erika (Oxford : Oxford University Press, 2022)
This text offers a fresh theoretical account of cities as federalism subjects, exploring the increased importance of cities in recent decades from political, economic, socio-cultural, and demographic perspectives.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2022).
Keywords: Federal-city relations; Federal government; Constitutional law; Politics and Government; Politics & government